Integrative Method of Learning Tahfidz Al Qur’an: Study at Utsman bin Affan Qur’an House Randublatung - Auliya, Alfa Firdausa; Romlah, Romlah; Mardiana, Dina (Postgraduate Program Magister Pendidikan Agama Islam, 2024)
The integrative methode in learning tahfidz Al Qur’an at the Utsman Bin Affan Qur’an House by integrating four method at one time, and among these methods are the Talaqqi, Jibril, Sima’i, and Tasmi’ Al Qur’an methods. The purpose of this study is to describe the integrative method in learning tahfidz Al Qur'an at Utsman Bin Affan Qur'an House. This research uses a qualitative approach, with the type of case study research, and the research location is conducted at the Qur'an House of Utsman Bin Affan Randublatung which integrates four methods at once in one learning time with different age levels of students. the informants of this research are one founder, two ustadzah and seven students of the Qur'an House of Utsman Bin Affan Randublatung, to get accurate and precise information researchers collect data by observation, interviews, and documentation. After that, researchers tested the validity of the data, and then researchers analysed the data with the stages of data reduction, data display, and conclusion drawing. From the results of the research, the integrative method in learning tahfidz Al Qur'an Utsman Bin Affan Randublatung maximises time efficiency, ustadzah collaboration, creating an environment that is conducive and comfortable for learning, utilising appropriate technology and periodic evaluations that help in strengthening memorisation.